Nowe środki społecznego przekazu a teoria ustawodawcza- współczesne problemy amerykańskiej wolności prasy - Lively, Donald E. (Wydział Prawa i Administracji UAM, 1993)
The article presents complex problems connected with the application of the First Amendment to the Constitution of the USA in the context of the appearance of new media and extensive transformations of the social life.
New media and regulatoiy theory. Modern problems in American freedom of the press